Sutures et traitements numériques - Campeau, Sylvain (Ciel variable)

(untitled) (Les Productions Ciel variable, 2007)
Joan Fonctuberta's latest body of work, Datascapes, is composed of two series: Orogenesis and Googlegrams. The first series was produced with software intended to produce photorealistic perspectives from topographical maps and satellite imagery. However, Fontcuberta fed the software with reproductions of artworks. The works in the second series are assemblages of thousands of small digital images, or tiles, found on the Internet through the Google search engine. All tiles in a single work responded to search criteria related to the larger composite picture. The author reads these works by Fontcuberta as instances of eternal displacements, in which the content of each image is yet another culturally produced image. As such, the content of these works continuously evades any fixed meaning and acquires significance only in the displacement itself.